2004
DOI: 10.1227/01.neu.0000134384.94749.b2
|View full text |Cite
|
Sign up to set email alerts
|

Lesion-induced Pseudo-dominance at Functional Magnetic Resonance Imaging: Implications for Preoperative Assessments

Abstract: Lesion-induced neurovascular uncoupling causing reduced fMRI signal in perilesional eloquent cortex, in conjunction with normal or increased activity in homologous brain regions, may simulate hemispheric dominance and lesion-induced homotopic cortical reorganization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(96 citation statements)
references
References 37 publications
3
89
0
4
Order By: Relevance
“…Ulmer et al proposed that lesion-induced neurovascular uncoupling causing reduced fMRI signal in perilesional eloquent cortex may simulate lesion-induced cortical reorganization. 31 On the other hand, in a more recent study, functional brain mapping using navigated transcranial magnetic stimulation showed that no plastic relocation of the primary motor cortex was observed in the 6 patients with AVMs near the rolandic region, even if the anatomy was severely obscured by the rolandic AVM. 21 Therefore, it seems that cortical reorganization on fMRI is not a significant predictor of surgical outcomes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Ulmer et al proposed that lesion-induced neurovascular uncoupling causing reduced fMRI signal in perilesional eloquent cortex may simulate lesion-induced cortical reorganization. 31 On the other hand, in a more recent study, functional brain mapping using navigated transcranial magnetic stimulation showed that no plastic relocation of the primary motor cortex was observed in the 6 patients with AVMs near the rolandic region, even if the anatomy was severely obscured by the rolandic AVM. 21 Therefore, it seems that cortical reorganization on fMRI is not a significant predictor of surgical outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…1) Pathophysiological factors, including gliosis, hemosiderosis, neovascularity, and AVM-induced hemodynamic effects, may cause neurovascular uncoupling and reduce fMRI signal in perilesional eloquent cortex. 31 2) Observational methods such as fMRI do not prove necessity or sufficiency of a particular area for function; instead, fMRI is only able to demonstrate a particular area's involvement in motor function. 1 3) White matter involvement could be contributing to and confounding the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors and congenital lesions may cause neurovascular coupling, compromising the blood oxygen level-dependent functional MR imaging signal in the regional eloquent cortex (2,5,(41)(42)(43). The area of motor cortex activation is influenced by the rate and force of contractions (44)(45)(46)(47)(48)(49)(50)(51).…”
Section: Figurementioning
confidence: 99%
“…This approach correlates well with intraoperative mapping (11) and the risk of motor postoperative deficits (4), and it can be used in conjunction with intraoperative localization techniques (12). Functional MR imaging is complementary to, although not a replacement for, these other methods of localization, including intraoperative electrocortical stimulation (2,5). Intraoperative electrocortical mapping also has limitations, however, particularly when the motor cortex is located deep within a sulcus and is not accessible to surface stimulation (13).…”
mentioning
confidence: 96%
See 1 more Smart Citation